Radiation losses in a periodically deformed single-mode fiber - Wlodarczyk, M.; Seshadri, S. (Journal of lightwave technology, 1987)
Scattering of the fundamental mode on a step-index fiber subject to microbendings is considered. An analytical technique is developed which is applicable to fibers with arbitrary numerical apertures, large deformation periods, and radiation escaping at arbitrary angles to the fiber axis. Low and high radiation orders are compared as a function of the length of deformation period. In the case of a fiber deformed by corrugated plates, the maximum radiation loss associated with the fundamental spatial harmonic of a microbending structure with a given period is equal to the maximum radiation loss associated with the nth spatial harmonic of the microbending structure with a period n times longer. Unlike in multimode fibers, microbending losses in single-mode fibers depend strongly on the wavelength of the light source. It is found that these losses vary critically with core radius. The scattered radiation is almost equally composed of the TE and TM polarized waves.